Organic Agriculture: A Global Perspective 2006
DOI: 10.1079/9781845931698.0259
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impacts of organic farming.

Abstract: This chapter provides an overview of the main indicators of environmental impact, i.e., biodiversity, landscape, soil, ground and surface water, climate and air, and energy. The discussion of environmental impacts is structured by six main sectors. Significant interrelationships were observed between these sectors. The effects of biological diversity are detailed for the following three aspects: genetic diversity, species diversity (floral and faunal) and habitat diversity. The soil aspect focuses on organic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…A recent position paper cautioned that critical ecosystem services such as pollination and pest control for food production both support and depend on biodiversity (MA 2003). The same linkages have been expressed for organic farming operations with higher biodiversity than conventional farms (Kasperczyk and Knickel 2006; Letourneau and van Bruggen 2006).…”
Section: Biodiversity and Critical Ecosystem Servicesmentioning
confidence: 85%
See 1 more Smart Citation
“…A recent position paper cautioned that critical ecosystem services such as pollination and pest control for food production both support and depend on biodiversity (MA 2003). The same linkages have been expressed for organic farming operations with higher biodiversity than conventional farms (Kasperczyk and Knickel 2006; Letourneau and van Bruggen 2006).…”
Section: Biodiversity and Critical Ecosystem Servicesmentioning
confidence: 85%
“…Certification regulations and government mandates commonly mention biodiversity as a goal or standard for organic agriculture (FAO 1999; Kasperezyk and Knickel 2006). Recent meta‐analyses and subsequent comparisons of organic and conventional farms show that organic agriculture can promote biodiversity in general and the diversity of predatory arthropods in particular.…”
Section: Biodiversity On Organic Versus Conventional Farmsmentioning
confidence: 99%
“…In agricultural landscapes, increased applications of fertilizers and pesticides have led to a degradation of habitats and losses in the biodiversity of several taxonomic groups. Organic farming, as an alternative to conventional farming, has been suggested to counteract such changes in community structure and function (reviewed by Bengtsson et al 2005; Hole et al 2005; Kasperczyk and Knickel 2006). Additionally, the insurance hypothesis predicts that a high diversity of natural enemies ensures the functioning of biological control because the larger number of species provide a greater guarantee that some species will maintain functioning if others fail in situations of environmental fluctuations (Yachi and Loreau 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Little evaluation of energy use in precision agriculture has been conducted; however, studies have consistently shown that application of any synthetic nitrogen fertiliser reduces energy efficiency when compared to organic systems that use manure or legumes as a nitrogen source (Aubert et al, 2003;Soil Association, 2006;Kasperczyk et al, 2006;Pimentel, 2006). A study from the Netherlands suggests that precision technology can reduce fertiliser input without sacrificing yields, but energy use in this system has not been evaluated (Koopmans et al, 2005).…”
Section: Mechanisationmentioning
confidence: 99%
“…There is an extensive body of research devoted to many environmental, social, and economic comparisons of organic and conventional agricultural systems. Various studies have compared the nutritional levels, yield, net income, quality of farmers' lives, and a variety of environmental impacts such as farmland biodiversity, soil quality, nutrient leaching, global warming potential, area of land used, and production in years with extreme weather conditions such as drought (Lotter, 2003;Kasperczyk et al, 2006;Stolze et al, 2000). This analysis does not aim to tackle the myriad factors on which these two systems can be compared.…”
Section: Factors Limiting the Analysis Of Energy Use In Agricultural mentioning
confidence: 99%